Far-red imaging of β-galactosidase through a phospha-fluorescein. Issue 88 (14th October 2020) - Ding, Zichao; Wang, Chuanfeng; Fan, Mengting; Zhang, Mengyuan; Zhou, Yao; Cui, Xiaoyan; Zhang, Dazhi; Wang, Ting
Abstract : The introduction of phosphine oxide into a fluorescein scaffold has yielded phospha-fluorescein with bathochromically shifted spectra, reliable photostability and solubility. Abstract : The introduction of phosphine oxide into a fluorescein scaffold has yielded phospha-fluorescein with bathochromically shifted spectra, reliable photostability and solubility. Moreover, ratiometric and turn-on fluorescence in the decaging process has ensured that the phospha-fluorescein is a unique scaffold for fluorescence bioimaging. Probe DiMe-PF-Gal without further structural decoration was designed for accurately monitoring β-galactosidase in vivo .